Global, regional, and national burden of cardiovascular diseases attributable to metabolic risks across all age groups from 1990 to 2021: an analysis of the 2021 global burden of disease study data - Xing-Yu Zhu; Miao-Qian Shi; Zhi-Meng Jiang; Xiao-Li; Jian-Wei Tian; Fei-Fei Su (BMC Public Health)
Abstract Objective The objective is to evaluate the temporal trends in the burden of cardiovascular diseases attributable to metabolic risk factors from 1990 to 2021 and to project the burden over the subsequent 30 years. Methods A joinpoint regression model was employed to estimate the annual percentage change in cardiovascular disease mortality attributable to metabolic risk factors, utilizing data from the Global Burden of Disease (GBD) 2021. An age-period-cohort analysis was conducted to evaluate the effects of age, period, and cohort. A frontier analysis was employed to investigate the correlation between the prevalence of cardiovascular disease attributable to metabolic risk factors and socio-demographic trends. An autoregressive integrated moving average (ARIMA) model was subsequently constructed to forecast future cardiovascular disease burden. Results Between 1990 and 2021, the global age-standardized mortality rate (ASMR) of cardiovascular diseases attributable to metabolic factors exhibited a consistent decline (Average Annual Percent Change (AAPC) = -1.28, 95% CI [-1.42, -1.14], P < 0.01). However, the absolute number of deaths increased from 8.326 million to 13.595 million. The most substantial reduction in ASMR was observed in the High Socio-Demographic Index (SDI) region (AAPC = -2.98, 95% CI [-3.10, -2.86], P < 0.01), whereas the reductions were relatively smaller in the Low-middle SDI and Low SDI regions. The ARIMA model predicts a decline in global cardiovascular disease mortality over the next three decades, with the most pronounced decrease anticipated in the high-middle SDI region and smaller declines expected in the middle SDI and low SDI regions. Conclusion Notwithstanding a global decline in age-standardized mortality and disability-adjusted life year (DALY) rates, the burden of cardiovascular diseases attributable to metabolic factors remains significant worldwide. Targeted interventions must be implemented without delay, particularly for males and populations in low and middle SDI regions, to mitigate the impact of metabolic factors on public health.